Beginning with criticism: An analysis of the first four volumes of Art South Africa - Snapper, Clarissa J. (My University, 2008)
Art South Africa is currently the leading, professionally published art magazine in South Africa. The magazine plays an important role in the dissemination of art discourse and art news and is the only ongoing, printed forum devoted exclusively to South African contemporary art. In this paper I will be looking at Art South Africa to describe the type of art texts it presents and the particular position it has taken in the contemporary art world of South Africa. In doing this I will be analysing the magazine to register the types of writing and other information in formats such as art news, exhibition reviews, artist bios, interviews and even advertising. This paper will also be analysing selected texts to determine the key issues that are represented and the way those issues have been represented with a critical position. Looking at Art South Africa from many angles will show that criticality is one of the magazine’s ideological aims and though the magazine’s format changes over time, it has continually sought to engage its readers in critical discourse.
Keywords: Art criticism; Art criticism- South Africa; Art South Africa (Journal Title)